A mysterious postoperative rash. (15th May 2018) - Chicco, Maria; Filobbos, George; Francis, Nicholas; Ziprin, Paul
Abstract : This case report describes the development of a rash in a patient admitted with large bowel obstruction secondary to carcinoma of the sigmoid colon. The patient underwent a Hartmann's procedure and right hemicolectomy for a metastatic deposit at the terminal ileum. On postoperative day 3, the patient developed a bullous haemorrhagic rash on the thighs, flanks and abdomen, associated with a sharp drop in platelet count. Suspicion of heparin-induced skin necrosis was raised, and prophylactic enoxaparin was switched to fondaparinux. Skin biopsy results later confirmed the diagnosis. Clinical suspicion of heparin-induced skin necrosis is essential and should prompt a switch between prophylactic agents, in order to prevent potentiation of this life-threatening side effect.